Targeting Inflammatory Processes Mediated by TRPVI and TNF-α for Treating Noise-Induced Hearing Loss - Dhukhwa, Asmita; Bhatta, Puspanjali; Sheth, Sandeep; Korrapati, Krishi; Tieu, Coral; Mamillapalli, Chaitanya; Ramkumar, Vickram; Mukherjea, Debashree (Frontiers in Cellular Neuroscience, 2019)
Noise trauma is the most common cause of hearing loss in adults. There are no known FDA approved drugs for prevention or rescue of noise-induced hearing loss (NIHL). In this study, we provide evidence that implicates stress signaling molecules (TRPV1, NOX3, and TNF-α) in NIHL. Furthermore, we provide evidence that inhibiting any one of these moieties can prevent and treat NIHL when administered within a window period. Hearing loss induced by loud noise is associated with the generation of reactive oxygen species (ROS), increased calcium (Ca2+) in the endolymph and hair cells, and increased inflammation in the cochlea. Increased (Ca2+) and ROS activity persists for several days after traumatic noise exposure (NE). Chronic increases in (Ca2+) and ROS have been shown to increase inflammation and apoptosis in various tissue. However, the precise role of Ca2+ up-regulation and the resulting inflammation causing a positive feedback loop in the noise-exposed cochlea to generate sustained toxic amounts of Ca2+ are unknown. Here we show cochlear TRPV1 dysregulation is a key step in NIHL, and that inflammatory TNF-α cytokine-mediated potentiation of TRPV1 induced Ca2+ entry is an essential mechanism of NIHL. In the Wistar rat model, noise produces an acute (within 48h) and a chronic (within 21 days) increase in cochlear gene expression of TRPV1, NADPH oxidase 3 (NOX3) and pro-inflammatory mediators such as tumor necrosis factor-α (TNF-α) and cyclooxygenase-2 (COX2). Additionally, we also show that H2O2 (100 µM) produces a robust increase in Ca2+ entry in cell cultures which is enhanced by TNF-α via the TRPV1 channel and which involves ERK1/2 phosphorylation. Mitigation of NIHL could be achieved by using capsaicin (TRPV1 agonist that rapidly desensitizes TRPV1. This mechanism is used in the treatment of pain in diabetic peripheral neuropathy) pretreatment or by inhibition of TNF-α with Etanercept (ETA), administered up to 7 days prior to noise exposure or within 24 h of noise. Our results demonstrate the importance of the synergistic interaction between TNF-α and TRPV1 in the cochlea and suggest that these are important therapeutic targets for treating NIHL.